Fabrication and Cell Responsive Behavior of Macroporous PLLA/Gelatin Composite Scaffold with Hierarchical Micro-Nano Pore Structure - Song, Kedong (2015)
Scaffolds providing a 3D environment which can effectively promote the adhesion, proliferation and differentiation of cells are crucial to tissue regeneration. In this study, the poly-l-lactic acid (PLLA) scaffold with hierarchical pore structural was fabricated via two-step thermally induced phase separation (TIPS). To mimic both physical architecture and chemical composite of natural bone extracellular matrix (ECM), gelatin fibers were introduced into the pores of PLLA scaffolds and formed 3D network structure via TIPS. Human adipose tissue-derived stem cells (ADSCs) were harvested and seeded into PLLA/gel hybrid scaffolds and cultured in vitro for biocompatibility assay. The surface morphology, porosity and compressive modulus of scaffolds were characterized by scanning electron microscopy (SEM), density analysis and compression test respectively. The results showed that hybrid scaffolds had high porosity (91.62%), a good compressive modulus (2.79 ± 0.20 MPa), nanometer fibers (diameter around 186.39~354.30 nm) and different grades of pore size from 7.41 ± 2.64 nm to 387.94 ± 102.48 nm. The scaffolds with mild hydrolysis by NaOH were modified by 1-ethyl-3-(3-dimethyl ami-nopropyl) carbodiimide/N-hydroxysuccinimide (EDC/NHS). Gelatin was performed onto PLLA scaffold via TIPS aiming at enhancement cell-material interaction. In comparison with PLLA scaffold, the PLLA/gel scaffold had better biological performance and the mechanical properties because the gelatin fibers homogeneously distributed in each pore of PLLA scaffold and formed 3D network structure.